1997
DOI: 10.1523/jneurosci.17-18-06864.1997
|View full text |Cite
|
Sign up to set email alerts
|

NAC-1, a Rat Brain mRNA, Is Increased in the Nucleus Accumbens Three Weeks after Chronic Cocaine Self-Administration

Abstract: Chronic cocaine use leads to biochemical and behavioral changes that can persist for weeks to months after drug administration is discontinued. Alterations in gene expression in the mammalian CNS may contribute to these long-term neural consequences of cocaine abuse. A combined in situ transcription-PCR amplification strategy was used to isolate a novel mRNA, NAC-1, from the nucleus accumbens of rats 3 weeks after discontinuing 3 weeks of intravenous cocaine self-administration. In rats that selfadministered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 37 publications
(46 reference statements)
3
72
0
Order By: Relevance
“…Although the relevance of changes in PENK mRNA levels elicited by cocaine self-administration and its extinction awaits further analysis of complementary changes in receptor function, the present results are in accordance with other studies showing that chronic cocaine administration produces long-lasting neuroadaptations in gene expression , especially in dopamine terminal fields (Hope et al 1994;Moratalla et al 1996;Cha et al 1997). Long-lasting behavioral alterations exist associated with cocaine addiction, including the development of paranoia and drug craving (Satel and Edell 1991;Childress et al 1999).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although the relevance of changes in PENK mRNA levels elicited by cocaine self-administration and its extinction awaits further analysis of complementary changes in receptor function, the present results are in accordance with other studies showing that chronic cocaine administration produces long-lasting neuroadaptations in gene expression , especially in dopamine terminal fields (Hope et al 1994;Moratalla et al 1996;Cha et al 1997). Long-lasting behavioral alterations exist associated with cocaine addiction, including the development of paranoia and drug craving (Satel and Edell 1991;Childress et al 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Repeated administration of cocaine can also regulate the activity of opioid receptors in discrete brain regions of rats. Indeed, it has been shown that 2 weeks of either continuous administration of cocaine via subcutaneously implanted osmotic mini-pumps (Hammer 1989) or repeated daily injections (Unterwald et al , 1994 lead to increase in and -opioid receptor density in terminal fields of the nigrostriatal and mesolimbic-mesocortical dopamine systems (for a review see Izenwasser 1998).Identification of the alterations in brain function by chronic cocaine administration has been a focus of many research efforts over the last two decades (for review see Nestler 1993;White et al 1995;Pierce and Kalivas 1997). This effort has consistently revealed the induction of many changes in cellular processes, although the data sometimes appear contradictory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments suggest that a DFosBCdk5 cascade and NAC1 may mediate a homeostatic negative feedback response to minimize the behavioral impact of subsequent stimulant administration. [39][40][41] In contrast to Cdk5 and NAC1, bFGF may play a significant role in establishing and/or sustaining sensitization because (1) the development of sensitization to amphetamine was blocked when the stimulant injections were preceded by infusions of a neutralizing antibody against bFGF into the VTA, 12 and (2) repeated coadministration of a nonselective glutamate receptor antagonist with amphetamine produced neither sensitization nor elevated bFGF expression. 42 To investigate the possible relation of Mrt1b with DFosB, Cdk5, NAC1 or bFGF would provide a clue to the molecular basis for an increase in mrt1b mRNA levels after repeated MAP.…”
Section: Discussionmentioning
confidence: 99%
“…Much is known regarding the immediate and short-term molecular and cellular consequences of stimulant drug exposure. In contrast, however, a far more limited number of persistent, long-standing cellular, or molecular adaptations to drug use have been described (Sorensen et al, 1982;Cha et al, 1997;Hope et al, 1994;Chen et al, 1997). Significantly, a clear link between known cellular adaptations and long-standing behavioral change has remained elusive.…”
Section: Introductionmentioning
confidence: 99%